Comparison of effects of cilnidipine and azelnidipine on blood pressure, heart rate and albuminuria in type 2 diabetics with hypertension: A pilot study. Issue 2 (22nd October 2012) - Abe, Hiroko; Mita, Tomoya; Yamamoto, Risako; Komiya, Koji; Kawaguchi, Minako; Sakurai, Yuko; Shimizu, Tomoaki; Ohmura, Chie; Ikeda, Fuki; Kawamori, Ryuzo; Fujitani, Yoshio; Watada, Hirotaka
Abstract Previous studies reported that both cilnidipine and azelnidipine have a renoprotective effect compared with amlodipine. The aim of this study was to compare the effects of cilnidipine and azelnidipine on blood pressure, heart rate and albuminuria. An open‐label prospective crossover trial was carried out. We recruited 19 type 2 diabetics treated with amlodipine (5 mg/day) at least for 12 weeks. At study entry, amlodipine was changed to cilnidipine (10 mg/day) or azelnidipine (16 mg/day) and each administered for 16 weeks. Then, the drugs were switched and the treatment was continued for another 16 weeks. Despite no differences in 24‐h blood pressure and heart rate between cilnidipine and azelnidipine, treatment with cilnidipine resulted in a greater reduction in urinary albumin:creatinine ratio than azelnidipine. Our results suggested that cilnidipine is more efficient in reducing albuminuria than azelnidipine independent of its blood pressure lowering effect in type 2 diabetic patients with hypertension. This trial was registered with UMIN (no. 000007201).